2007
DOI: 10.1093/molbev/msm024
|View full text |Cite
|
Sign up to set email alerts
|

Functional Divergence in the Arabidopsis  -1,3-Glucanase Gene Family Inferred by Phylogenetic Reconstruction of Expression States

Abstract: Plant beta-1,3-glucanases (beta-1,3-Gs) (E.C. 3.2.1.39) comprise large, highly complex gene families involved in pathogen defense as well as a wide range of normal developmental processes. In spite of previous phylogenetic analyses that classify beta-1,3-Gs by sequence relatedness, the functional evolution of beta-1,3-Gs remains unclear. Here, expression and phylogenetic analyses have been integrated in order to investigate patterns of functional divergence in the Arabidopsis beta-1,3-G gene family. Fifty beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
151
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(165 citation statements)
references
References 58 publications
6
151
1
1
Order By: Relevance
“…According to phylogenic analyses, the GH17 family is divided into three distinct clades (denoted α, β, and γ) [61,62], with 10% of its members having cell wall-related functions [61]. GH17 of the α clade are more related to stem elongation, but also responsive to gibberellin, those of the β and γ clades are more related to stress response and defense against pathogens [62][63][64][65].…”
Section: Gh 17mentioning
confidence: 99%
See 2 more Smart Citations
“…According to phylogenic analyses, the GH17 family is divided into three distinct clades (denoted α, β, and γ) [61,62], with 10% of its members having cell wall-related functions [61]. GH17 of the α clade are more related to stem elongation, but also responsive to gibberellin, those of the β and γ clades are more related to stress response and defense against pathogens [62][63][64][65].…”
Section: Gh 17mentioning
confidence: 99%
“…GH17 of the α clade are more related to stem elongation, but also responsive to gibberellin, those of the β and γ clades are more related to stress response and defense against pathogens [62][63][64][65]. In addition to the GH17 domain per se, proteins of the GH17 family comprise other domains as shown by [61] studying the β-1,3-glucanase sequences of A. thaliana. They noted that all the sequences had a predicted N-terminal signal peptide linking them to the secretory pathway.…”
Section: Gh 17mentioning
confidence: 99%
See 1 more Smart Citation
“…Although only the A6 gene was thought to be a potential major component of the callase enzyme mixture (Hird et al, 1993), Arabidopsis has .50 genes encoding putative b-1,3-Gs (Doxey et al, 2007), suggesting that the metabolism of b-1,3-glucan in plants is more complex than previously understood. We identified three other b-1,3-G genes (At3g24330, At3g55780, and At3g61810) showing different extents of reduced expression in cdm1, including two anther-specific ones (Supplemental Fig.…”
Section: Callose Dissolution During Pollen Development Is a Highly Comentioning
confidence: 99%
“…In Lilium, it was shown that endo-b-1,3-Gs were responsible for callose wall degradation during microsporogenesis (Stieglitz, 1977). Although the Arabidopsis genome has .50 genes encoding b-1,3-Gs (Doxey et al, 2007), only the A6 gene was suggested to be a major component of the callase mixture secreted by the tapetum (Hird et al, 1993). Among known regulatory genes for anther development, only the AtMYB80 (formally AtMYB103) gene encoding a putative transcription factor was identified as a positive regulator of the A6 gene, affecting callose metabolism during microsporogenesis .…”
mentioning
confidence: 99%